Valuing Information Security: A Look at the Influence of User Engagement on Information Security Strength. Issue 3 (3rd July 2017) - Boyle, Randall J.; Challa, Chandrashekar D.; Clements, Jeffrey A.
ABSTRACT: This study looks at the influence of user engagement on users' information security practices. A model describing how user engagement (user posts) may influence a person's decision to employ better security measures (stronger passwords) is tested. Password strength was determined by looking at password length, the types of characters used, the variety of character sequences used, the number of duplicate passwords, and the number of uncrackable passwords. Passwords were tested using a variety of cracking techniques. This study found that individuals from an online gaming site who made more posts to the user forum employed stronger passwords.